Determinan Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) pada Akseptor KB - Indah Budiarti; Dina Dwi Nuryani; Rachmat Hidayat (Politeknik Kesehatan Tanjung Karang, 2017)
The main problem that Indonesia faces in demography is the high population growth. Efforts in realizing quality family has the main goal to control the population growth and to improve the quality of small size family which is indicated with the use of rational, effective and efficient birth control method, the long term birth control method (LTBCM). Kalirejo public health center in gaining LTBCM tended to decrease in the last two years from 10,87% to 10,62%. The pre-survey result in October 2016 showed reduced LTBCM of 377 fertile age couples (10,62%) from 3555 birth control acceptors. The objective of this research was to find out the determinants of a long term birth control method used in the birth control acceptors in Kalirejo public health center working area in Negeri Katon sub district of Pesawaran in 2017. This was an analytic research with cross sectional approach. The research population was all active birth control acceptors in Kalirejo public health center with 360 samples of acceptors of LTBCM and non- LTBCM. Primary data were collected with questionnaires and analyzed by using univariate, bivariate and multivariate analyses. The research results showed that 75,3% respondents used non-LTBCM, 57,2% risks not to use LTBCM, 56,7% unemployed, 65,3% respondents were in risks to have more children, 83,6% respondents were supported by their couples. Bivariate analysis result found correlations of age (p=0,007), occupation (p=0,000), couple’s support (p=0,000), to the use of LTBCM. Amount of child (p=0,208) did not correlate with the use of LTBCM. The researcher recommends that the local public health centers should conduct education of the active birth control acceptors to use the LTBCM as the role models for new acceptor candidates which in turn will enhance the coverage of the LTBCM services in their working areas.